4 - Condolences to BUJRA’s Family and to CODESRIA - Taladidia Thiombiano, (CODESRIA Bulletin, 2025)
My condolences to the family of the distinguished deceased and also to CODESRIA. He was one of the great builders of CODESRIA. May young researchers remember him. Like Samir Amin, Thandika and many others. You did not live a useless life on this earth. Rest in peace!